2020
DOI: 10.1101/2020.06.07.138800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic analysis of SARS-CoV-2 isolates collected from Bangladesh: insights into the origin, mutation spectrum, and possible pathomechanism

Abstract: As the coronavirus disease 2019 , caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), rages across the world, killing hundreds of thousands and infecting millions, researchers are racing against time to elucidate the viral genome. Some Bangladeshi institutes are also in this race, sequenced a few isolates of the virus collected from Bangladesh. Here, we present a genomic analysis of 14 isolates. The analysis revealed that SARS-CoV-2 isolates sequenced from Dhaka and Chittagong were the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Although their direct evolution from that reference Wuhan virus was not found. So, it can be suggested that viruses from different regions other than China might also contribute to the SARS-CoV-2 outbreak in Bangladesh, which was also previously reported by Parvez et al 2020;Hasan et al 2020. Besides, that majority of the Bangladeshi isolates were found to fall within the clade B belonging to L type (Supplementary Table ST2).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although their direct evolution from that reference Wuhan virus was not found. So, it can be suggested that viruses from different regions other than China might also contribute to the SARS-CoV-2 outbreak in Bangladesh, which was also previously reported by Parvez et al 2020;Hasan et al 2020. Besides, that majority of the Bangladeshi isolates were found to fall within the clade B belonging to L type (Supplementary Table ST2).…”
Section: Discussionsupporting
confidence: 61%
“…To infer the evolutionary relationships among the examined sequences, the sequences were aligned with relevant reference sequences retrieved from NCBI database using the neighborjoining approach (Rahman et al, 2020). The Molecular Evolutionary Genetics Analysis across…”
Section: Phylogenetic Analysis Of Sars-cov-2 Sequencesmentioning
confidence: 99%
“…As for instance, one study reported analyses of 60 SARS-CoV-2 genome sequences from Bangladesh and compared them with 6 Southeast Asian countries ( Islam et al, 2020 ). Another group analyzed only 14 isolates and found 42 mutations ( Parvez et al, 2020 ). A separate study identified only 9 variants where unique mutations (UMs) were found prevalent mostly in ORF1ab ( Hasan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 47 Parvez and colleagues' molecular docking analysis revealed no significant interactions between the putative RNA binding site and the genome. 48 Doga Eskier et al reported that the third most common RdRp, 15324C>T, decreased the mutation rate created by RdRp, while the 14408C>T mutation had the opposite effect. They also suggested that the 14408C>T mutation contributed to co-mutations' dominance in Europe and elsewhere.…”
Section: Discussionmentioning
confidence: 99%